Numerical Study of Bottleneck Flow with Varying Corridor Width and Motivation Using a Speed-Based Model - Rzezonka, Jonas; Seyfried, Armin; Hein, Ben; Chraibi, Mohcine; Schadschneider, Andreas (Collective Dynamics, 2022)
In this study a simple speed-based model is employed to simulate an experiment of pedestrian bottleneck flow. The experiment revealed that the density near the bottleneck is influenced by the motivation of the pedestrians and the corridor width. In narrow corridors, distinct lanes are formed for pedestrians with low motivation. These lanes can disappear when the pedestrians have a high motivation to reach their target. We show that a speed-based model is - despite its relative simplicity- capable to reproduce the observed phenomena to a high degree.